The Relationship between Family Support and Involvement in Repeated Care for Mentally Ill Patients - Satria Jati Bawono; Wita Oktaviana (Indonesian Journal of Global Health Research, 2025)
Family support in caring for patients with mental disorders is the active involvement of family members in providing care, attention, and understanding of the patient's condition. This support includes understanding the patient's mental condition, helping manage medication, creating a supportive environment for recovery, and providing psychological encouragement to improve quality of life. The study aims to determine the relationship between family support involvement in repeated care for patients with mental disorders in the Grogol Community Health Center, Sukoharjo Regency. This type of research uses a quantitative research method. This study uses a descriptive correlation design with a Cross Sectional approach. In this study, researchers took samples by accidental sampling. In this study, the number of samples used was 45 samples. Data collection by distributing questionnaires through two instruments consisting of the Family Support Questionnaire and Repeated Care Questionnaire which were proven valid (0.217) with a Cronbach's Alpha reliability value above 0.7 considered good, indicating that the items in the questionnaire have adequate consistency. Data were analyzed using the Spearman's Rank test. The results of this study indicate a significant relationship between family support and repeated care with a P-Value of 0.013.